Assessment of Rational Prescribing and Relative Cost of Antibiotics for In-Patients Treated in Selected Tertiary Health Care Facilities in Southern Nigeria - Patrick O Erah, MPharm, PhD; Mary O Ehiagwina, PharmD (International Journal of Pharma and Bio Sciences, 2010)
This study was undertaken to evaluate rational prescribing and cost of antibiotics in four referral healthcare facilities in Edo State. In a retrospective cross-sectional study, prescriptions of 800 systematically selected inpatients who received antibiotics therapy were evaluated. Prescribing indicators, DDDs and local costs of the antibiotics expressed in a ratio of the international prices as “median price ratio” (MPR) were evaluated. Number of antibiotics per encounter, percentages prescribed by generic name and encounter with injection, proportions of antibiotics essential drugs list and those used for prophylaxis were 1.81±0.01, 45.31±8.70%, 77.07±3.34%, 92.75±1.77% and 47.25±0.35%, respectively. Either relatively too low or high doses were used in most cases. MPR varied from 0.15 to 14.32 with 87.5% of the antibiotics having prices much higher than the international prices. It is concluded that inappropriate use of antibiotics still exists in the health facilities and most antibiotics cost several times more than the international prices.